КӨКӨЗЕК БОЛЫСЛЫҒЫНЫҢ ХАЛЫҚ СУДЫ АРЗЫМБЕТ ҚАЗЫ ИСКЕРЛИГИ ҲАҚҚЫНДА - Опаев, Баймурат Абдрешитович (FAN va JAMIYAT, 2026)
This article chronicles the life and socioeconomic activities of the renowned people’s judge Arzymbet Qazi, who served in the Kukuzyak volost in the late 19th and early 20th centuries. It provides information on the judicial activities of Arzymbet Qazi and his efforts to improve the lives of his people.